Antithrombotic Therapy in Spinal Surgery Does Not Impact Patient Safety–A Single Center Cohort Study - Banat, Mohammed; Wach, Johannes; Salemdawod, Abdallah; Bara, Gregor; Shabo, Ehab; Scorzin, Jasmin E.; Müller, Martin; Vatter, Hartmut; Eichhorn, Lars (Frontiers in Surgery, 2022)
Objective Oral anticoagulation (OAC) is common in older patients to avoid thromboembolic events. Careful planning is required, particularly in the perioperative environment. There are no clearly date guidelines on the best timing for interrupting the use of anticoagulation in the case of spinal surgery. This study evaluates clinical outcomes in patients whose OAC was interrupted for spinal surgery. Methods This is a retrospective cohort study. All patients who underwent dorsal instrumentation from January 1, 2019 to December 31, 2020 were included. In group A, vitamin K antagonists (VKA) were suspended for 5 days and direct oral anticoagulants (DOAC) for 3 days. In group B, antiplatelet agents (APA) were paused for at least 7 days before surgery to prevent perioperative bleeding. Patients not taking anticoagulation medication were gathered into control group C. We analyzed demographic data, ASA status, blood loss, comorbidities, duration of surgery, blood transfusion, length of hospital stay, complications, thromboembolism, and 30 day in-hospital mortality. Multivariate analyses from the three groups were further analyzed and conducted. Results A total of 217 patients were operated and included. 28 patients taking VKA/DOAC (group A), 37 patients using APA (group B), and 152 patients without anticoagulation (group C) underwent spinal surgery. Those using anticoagulants were significantly older and often with multimorbidity, but did not differ significantly in procedural bleeding, time of surgery, length of hospital stay, complication rate, thromboembolism, or 30 day in-hospital mortality (p>0.05). Conclusion Our data show that dorsal instrumentation safely took place in patients whose anticoagulation was interrupted.